Settlement Of Crimes Of Persecution Through Restorative Justice In The Jurisdiction Of The Bali Regional Police - I Gede Yoga Mahardiana; Erikson Sihotang; I Nyoman Suandika (International Journal Labs, 2024)
The Indonesian state is a state of law, based on Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. This means that within the Unitary State of the Republic of Indonesia, the law must be upheld and become a means of carrying out activities in all aspects of national and state life. Laws that uphold human rights and guarantee equal status before the law are required to respond to all problems and conflicting interests of society. The problem formulation is how to resolve criminal acts of abuse through restorative justice in the Bali regional police? And what are the obstacles in resolving criminal acts of abuse through restorative justice in the Bali regional police? The research method in this case is empirical research, descriptive research, the data source is primary data; secondary data; and tertiary data, data collection techniques namely observation; interview; and documentation, and data processing and data analysis techniques, namely descriptive qualitative. Resolving criminal acts of abuse through Restorative Justice in the jurisdiction of the Bali Regional Police is carried out by integrating three forms of law enforcement, namely preemptive, preventive and repressive. However, the obstacles to this resolution are the lack of eyewitnesses, lack of human resources for law enforcement, and the trauma suffered by victims which is difficult to remove, so psychological support and long-term therapy are really needed to help victims recover emotionally and mentally.